Companion to an untold story - Aldrich, Marcia (University of Georgia Press, 2012)
When Marcia Aldrich's friend took his own life at the age of forty-six, they had known each other many years. As part of his preparations for death, he gave her many of his possessions, concealing his purposes in doing so, and when he committed his long-contemplated act, he was alone in a bare apartment. In Companion to an Untold Story, Aldrich struggles with her own failure to act on her suspicions about her friend's intentions. She pieces together the rough outline of his plan to die and the details of its execution. Yet she acknowledges that she cannot provide a complete narrative of why he killed himself. The story remains private to her friend, and out of that difficulty is born another story- the aftershocks of his suicide and the author's responses to what it set in motion. This book, modeled on the type of reference book called a "companion," attempts to find a form adequate to the way these two stories criss-cross, tangle, knot, and break. Organized alphabetically, the entries introduce, document, and reflect upon how suicide is so resistant to acceptance that it swallows up other aspects of a person's life. Aldrich finds an indirect approach to her friend's death, assembling letters, objects, and memories to archive an ungrievable loss and create a memorial to a life that does not easily make a claim on public attention. Intimate and austere, clear eyed and tender, this innovative work creates a new form in which to experience grief, remembrance, and reconciliation.